If it's not what You are looking for type in the equation solver your own equation and let us solve it.
4(x+3)+3(x+1)=36
We simplify the equation to the form, which is simple to understand
4(x+3)+3(x+1)=36
Reorder the terms in parentheses
+(+4x+12)+3*(x+1)=36
Remove unnecessary parentheses
+4x+12+3+*(+x+1+)=+36
Reorder the terms in parentheses
+4x+12+(+3x+3)=36
Remove unnecessary parentheses
+4x+12+3x+3=+36
We move all terms containing x to the left and all other terms to the right.
+4x+3x=+36-12-3
We simplify left and right side of the equation.
+7x=+21
We divide both sides of the equation by 7 to get x.
x=3
| 3h+k=-1 | | https://www.google.com/search?q=5(5-2x)-6(2-x)=7(1-x) | | e^7x+9=14 | | -2(4s-4)-8=-2(6s+11)-2 | | 3y+12=7y-4 | | 2/3x-1/2=-1 | | 1000(8x-10)=40(940+100x) | | 3(2-9x-8x)+8(6x+3)=12 | | -5(x^2-4)+7=2x+9 | | 2lnx+3lnx+5lnx=10 | | v/2=7 | | -5(x^2-4)+7=2+9 | | 1000(9x-10)=50(848+100x) | | 2r=-10r-8(1-2r) | | 3x-4(2x-5)-5x=3x+7 | | 25x+15y=28000 | | (2-3x)-(4x-7)= | | 2w-2x-y+7w+14x-7y= | | 12-(4-3x)=21 | | 2(x+4)=9x+7-7x+1 | | 7x-2y+12w+6y-3w+5x= | | 4g+12=1g+2 | | 6n+3n=9 | | 2m^2+2n^2-6m-2n-8=0 | | 6w+7y+3x+9x-15y+3w= | | (3x-1)(ax+b)=12x^2-19x+c | | 12-(14-3x)=21 | | 2w+2x-11y+7w+10x+3y= | | 120=-8-8(p-8) | | (3x-1)(ax+b)= | | 1520-40y=1150+28y | | i=ec/3 |